Conceptualization of Agro-Ecotourism Based Environmental Accounting in Jeneponto District - Alam, Syamsu; Tenriwaru, Tenriwaru; Ariaty Arfah, Eka (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023)DO - 10.24843/JIAB.2023.v18.i02.p07, 2023)
This study aims to frame the agro-tourism landscape in Jeneponto Regency as a sought-after tourist locale while also positioning environmental accounting as an effective tool for raising public awareness. Utilizing a case study methodology, the research was conducted in Jeneponto Regency. The participants were selected using a snowball sampling technique. Primary data, consisting of opinions and observational findings, were collected through in-depth interviews with subject matter experts and Focus Group Discussions (FGDs). Secondary data were sourced indirectly through intermediary mediums and augmented by a thorough document analysis. The data analysis process encompassed techniques such as data reduction, data display, and the subsequent drawing of conclusions and verification. The study sample was determined by the scope of the FGD, which included six respondents. A hallmark of this research is its comprehensive approach to accounting analysis. This approach extends from evaluating investment financing calculations for financial viability to assessing environmental costs and culminates in the formulation of financial reporting. The overarching goal is to elucidate the feasibility, profitability, and long-term sustainability of agro-ecotourism ventures. Keywords : agro-ecotourism, environmental accounting, jeneponto